PENGGUNAAN KOMBINASI METODE PEMBELAJARAN KONVENSIONAL DAN MODERN DI RA MUSLIMAT NU 15 SUKUN MALANG - Anis Susi Adila; Mohammad Afifulloh; Yorita Febry Lismanda (UNISMA, 2020)
The research that conducted is about the combination of traditional method and modern method in Raudhatul Athfal Muslimat NU 15 Malang. The research method used is qualitative research. The data collection techniques used are observations, interviews and documentation. The traditional method has been used where teacher just doing transters knowledge to students. Students become passive, their potential cannot be explored properly. The traditional method in RA Muslimat NU 15 Malang Is lecture method. The modern method is the methods that can cover all aspects of child development. The modern method in RA Muslimat NU 15 Malang are storytelling, assignment, demonstration, projects, question and answer, and role playing. The use of combination of traditional method and modern method is learning methods that combine traditional learning and modern learning. It aiming the teacher learning is not monotouns, students are not bored, the learning process becomes fun and talents and interests of children can be explored.